ANALISIS PERILAKU ETIS AUDITOR DENGAN PERSPEKTIF FILOSOFI TRI KAYA PARISUDHA - Ni Putu Ari Aryawati; Ni Made Chandri Aryawati; John Abraham Ziswan Suryosumunar; Dewa Oka Ayu Oki Astarini (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2021)
This study examine the philosophy of tri kaya parisudha on auditor’s ethical behavior. Tri kaya parisudha is one of Hindu’s ethics philosophy on Sarasamuccaya Sloka 74-76. Ethics value on auditing world be a focus and must be regulated by a code of ethics. The research background by phenomenon of bribery cashes and added corruption list in Indonesia. Auditor’s code ethics be the fundamental for carry out the task of auditing process for force dilemma heave in sight on judgment and decision of audit result. Data collection by book study and interview to university’s internal auditor. The simultan results show that tri kaya philosophy has an ability on auditor’s ethical behavior. Parsial results are manacika parisudha has positive effect on auditor’s ethical behavior; wacika parisudha has positive effect on auditor’s ethical behavior; and kayika parisudha has positive effect on auditor’s ethical behavior. The moral and ethical values ​​contained encourage auditors to act in accordance with the code of ethics and auditing principles while maintaining their integrity. The dilemma that occurs when the auditor make a decision and statement becomes distorted after the individual adheres to the values ​​of the tri Kaya parisudha. Interconnection link from tri kaya parisudha be a ethical fundamental for thinking , speaking and acting.